A new droplet breakup phenomenon in electrokinetic flow through a microchannel constriction. Issue 10 (14th June 2019) - Ji, Xiang; Zhou, Teng; Deng, Yongbo; Shi, Liuyong; Zhang, Xianman; Woo Joo, Sang
Abstract: A completely new droplet breakup phenomenon is reported for droplets passing through a constriction in an electrokinetic flow. The breakup occurs during the droplet shape recovery process past the constriction throat by the interplay of the dielectrophoretic stress release and the interface energy for droplets with smaller permittivity than that of the ambient fluid. There are conditions for constriction ratios and droplet size that the droplet breakup occurs. The numerical predictions provided here require experimental verification, and then can give rise to a novel microfluidic device design with novel droplet manipulations.